The Investigation of Serum Lipoprotein(a), Homo-cysteine and Malondialdehyde levels in non-insulin dependent diabetes mellitus (type 2) patients with and without diabetic complications - Gürsu, M. Ferit; Kılıç, Nermin; Çıkım, Gürkan; Doğan, Halil (Fırat University, 2001)
The aim of this study was to investigate serum lipoprotein(a) [Lp(a)], homocysteine and malondialdehyde (MDA) levels in NIDDM (type 2) patients with and without complications. A total of 49 NIDDM patients diagnosed with diabetes mellitus with mean age of 56±9 were included to this study. Control group was composed of 14 healthy volunteers. Group I consisted of 33 NIDDM patients with complications while group II consisted of 16 patients without complication. There was a statistically significant difference in homocysteine, lp(a) and MDA levels between group I and group II (p

Bu çalışmada komplikasyonlu ve komplikasyonsuz NIDDM'lu (tip 2) hastalarda serum lipoprotein (a) [Lp(a)], homosistein ve malondialdehit (MDA) düzeylerinin araştırılması amaçlanmıştır. Çalışma, diabet tanısı konulan yaş ortalamaları 56±9 olan toplam 49 NIDDM'lu hasta ve kontrol grubu olarak alınan 14 sağlıklı kişide yapılmıştır. Grup I, komp-likasyonlu 33 diabet Grup II, komplikasyonsuz 16 diabet hastasından oluşmuştur. NIDDM'lu komp-likasyonu olan Grup I' in serum homosistein, lp(a) ve MDA düzeyleri Grup II ile karşılaştırıldığında istatistiksel olarak anlamlı farklılıklar saptanmıştır (p
KOMPLİKASYONLU VE KOMPLİKASYONSUZ TİP 2 DİYABETLİ (NIDDM) HASTALARDA SERUM HOMOSİSTEİN VE LİPOPROTEİN(A) İLE MALONDİALDEHİT DÜZEYLERİNİN ARAŞTIRILMASI